Artificial intelligence and the social dimension of sustainable development: through a security perspective - Irja Malmio (Discover Sustainability)
Abstract Artificial Intelligence (AI) has been described as a great hope but also a threat to fulfilling the social goals of sustainable development, where one critical aspect is providing society with a safe and secure environment. At the same time, interdisciplinary analyses that connect the social effects of artificial intelligence with security issues have been relatively sparse. Accordingly, this article explores how the sociotechnical connection between AI, the social dimension of sustainable development, and security is being communicated in research conceptualizing this liaison. Conducive to this aim, a scoping review has been applied to holistically connect AI, social sustainability, and security while deploying a thematic content analysis to illustrate the central themes of this intersection. In total, 62 articles and eleven reports were included in the study. Six themes are explored: AI for social good, economic security, development and humanitarian aid, values, sociotechnical harms, and societal security. The article emphasizes the importance of aligning technology development with broader social objectives by highlighting the complex interplay between AI, social sustainability, and security. Understanding this link opens possibilities for developing AI solutions that contribute to social sustainability while identifying propensities in emerging technologies that can lead to ‘‘sociotechnical harm’’ with increased polarization and a deteriorated security situation.